Proposals for the Organization of International Logistics Activities of Agricultural and Agro-Processing Enterprises During the War Period - Liashenko, V.; Trushkina, N.; Lukianov, A.; Serbina, T. (Економічний вісник Донбасу, 2022)
The agricultural sector is the driver and “point of growth” of the national economy of Ukraine. Agriculture accounts for an average of 16% of gross value added in some regions and play a key role in ensuring food security. However, the current conditions of martial law in Ukraine have led to problems in the organization of logistics activities of enterprises of the agro-industrial complex as a result of non-fulfilment of the terms of contracts; emergence of risks of disruption of the sowing campaign; decrease in final harvest indicators and the level of food security; decrease in the volume of export deliveries of agricultural products; disruption of food supply chains; lack of adequate financing and logistics infrastructure facilities; insufficiently effective use of marketing management tools and a network approach in the process of distributing agricultural products to the final consumer; increase in transaction costs, etc. The article provides a statistical analysis of the main indicators of the development of foreign economic activity of enterprises of the agro-industrial complex of Ukraine in the pre-war period. Barriers that inhibit the effective organization of international logistics activities of agrarian enterprises in wartime have been identified. Priority directions for eliminating existing barriers that prevent the organization of foreign economic logistics activities are proposed, the essence of which is to activate network interaction and partnership relations based on the creation of agro-cluster structures; unification of small farms for the proper execution of contracts, as well as joint activity in the agrarian sphere of two or more companies and different groups of stakeholders to achieve a common goal and a synergistic effect. Аграрний сектор є драйвером і «точкою зростання» національної економіки України. Сільське господарство формує у деяких регіонах у середньому 16% валової доданої вартості та відіграє ключову роль у забезпеченні продовольчої безпеки. Однак сучасні умови воєнного стану в Україні призвели до проблем організації логістичної діяльності підприємств агропромислового комплексу унаслідок невиконання умов контрактів; появі ризиків зриву посівної кампанії; зменшення фінальних показників врожаю та рівня продовольчої безпеки; зниження обсягів експортних поставок сільськогосподарської продукції; порушення ланцюгів постачання продовольства; відсутності належного фінансування та об’єктів логістичної інфраструктури; недостатньо ефективного використання інструментарію маркетингового менеджменту і мережевого підходу в процесі розподілу аграрної продукції до кінцевого споживача; збільшення трансакційних витрат тощо. У статті виконано статистичний аналіз основних показників розвитку зовнішньоекономічної діяльності підприємств агропромислового комплексу України у довоєнний період. Виявлено бар’єри, які гальмують ефективну організацію міжнародної логістичної діяльності аграрних підприємств у воєнний час. Запропоновано пріоритетні напрями усунення існуючих бар’єрів, що перешкоджають організації зовнішньоекономічної логістичної діяльності, суть яких полягає в активізації мережевої взаємодії та партнерських взаємовідносин на основі створення агрокластерних структур; об’єднання дрібним фермерських господарств для належного виконання контрактів, а також спільної діяльності в аграрній сфері двох або більше компаній і різних груп стейкхолдерів для досягнення загальної мети і синергетичного ефекту.